Editorial (diségno, 2018)
Last year, just a few days before Christmas, Rony Abovitz’sstartup Magic Leap finally presented something concretein regards to the mysterious, so-called ‘mixed reality,’ saidto surpass both virtual reality and augmented reality. Thecompany has been working on the project since 2011, inFlorida, in great secrecy and with huge capital-risk financingby some of the major companies in the digital world, amongothers (more than two billion dollars have been raised todate). Basically, this revelation raised only a corner of theveil which, up to then, had hidden the invention, of whichonly a few bits of advance information, well-crafted to arousecuriosity and interest, had previously been disclosed.